2012 Framework on Public Compensation for SGEIs: Application in the Postal Sector. Issue 3 (September 2013) - Geradin, Damien; Malamataris, Christos
The legal rules applicable to State compensation for services of general economic interest ("SGEIs") were recently revised by the European Commission. This led to the adoption of the "2012 SGEI Package". The most contentious document of this Package, the "2012 Framework", sets out the conditions for the compatibility of SGEI compensation with the internal market. Against this background, the Commission has recently shown an increased interest in the application of the State aid rules to the postal sector and seems determined to continue scrutinizing the sector in the future. This article aims to analyse the specific rules of the Framework and look closer at the way they (could) apply to the postal sector, with references to the decisional practice of the Commission.